Satisfaction among Teaching and Nonteaching Staff Regarding Human Resource Practices and Employee Job Performance - Shaheen, Faiza; Kashif, Mahvish Fatima; Shumaila (Annals of Human and Social Sciences, 2023)
The study aimed to investigate the satisfaction level of teaching and nonteaching staff regarding human resource practices in terms of recruitment and selection, training and development, performance appraisal and compensation. The cross-sectional survey design was employed to carry out this study. The researcher used a self-developed instrument comprising of four practices of human resource management and employee performance. Both cadres of teaching and nonteaching staff were selected for the purpose of the study. Out of 150 employees, number of teaching staff was 72 and non-teaching staff were 78. The major objective of the study was to compare the satisfaction level of teaching and nonteaching staff regarding human resource practices. The quantitative analysis inferred the same satisfaction level regarding HR practices of both cadres. Furthermore, there was no significant difference (p > .05) found in the perception of teaching and nonteaching staff regarding HR practices. Relevant suggestions include improving human resource practices among employees.